(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
With changes in the pattern of life or habits of the community caused by the outbreak of the Covid-19 virus in Indonesia, such as the prohibition of crowding and the recommendation to stay at home which makes people stay at home more often, gardening, especially hydroponic gardening, can is one of the activities that can be useful in filling spare time while at home, besides gardening it also has promising business potential. The so-called hydroponics is a method of farming using other planting media besides soil.In connection with the still outbreak of the Covid-19 virus in Indonesia, especially in the city of Bandung and its surroundings, this time community service activities are carried out virtually (online) through the Zoom application, in order to keep the event interactive and to avoid boredom from the participants, So in addition to the presentation of the material from the speakers, this time, community service activities also combine talkshow styles so that participants can be more interactive and better understand the material that has been delivered.PKM activities that have been implemented have reached the expected targets in terms of the number of participants, the material presented, and the achievement of the objectives of the activity. By participating in this PKM activity, participants can better understand the ins and outs of the hydroponic business, and indirectly increase motivation from within the activity participants to become a hydroponic business entrepreneur.